Effect of Applying the Problem-Based Learning (PBL) Model with Powtoon Assessment Media on High School Students' Physics Learning Outcomes - Wati, Galuh Rahma Eka; Maryani, Maryani; Meilina, Ike Lusi (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2025)
Physics learning in senior high schools often faces challenges due to monotonous teaching methods and a lack of interesting media, resulting in low student interest and learning outcomes. This study aims to determine the effect of implementing the Problem-Based Learning (PBL) model supported by Powtoon-based assessment media on students' physics learning outcomes. Powtoon provides visual animations that can improve students' conceptual understanding. This study employed a quasi-experimental method with a post-test only control group design. The subjects were 72 eleventh-grade students at Arjasa State High School, randomly divided into 36 students in the experimental group and 36 students in the control group. The independent variable in this study was the PBL model with Powtoon media, the dependent variable was students' physics learning outcomes, and the control variables were the same topic and duration of instruction. The instrument used was a test consisting of essay questions. Data analysis was conducted using an independent sample t-test with a significance level of 0.05. The results of the study indicate a significant difference between the learning outcomes of students in the experimental group and the control group, with the experimental group achieving higher scores. Therefore, it can be concluded that the implementation of the PBL model with Powtoon as an assessment medium has a positive effect on students' physics learning outcomes. This approach can be used by teachers to enhance students' conceptual understanding and engagement in physics learning.